2020
DOI: 10.1186/s12913-020-05842-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and dental hygienists in Italy: a questionnaire survey

Abstract: Objective This online cross-sectional survey assesses the signs/symptoms, the protective measures taken and the awareness and risk perception regarding COVID-19 among Italian dental hygienists. All Italian dental hygienists were invited to participate. The ad hoc online questionnaire was divided into four domains: personal data, protective measures (−before patient arrival; −in the waiting room; −in the operating room) and PPE, awareness and risk perception. Results Two-thousand-seven-hundred-ninety-eight su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 16 publications
(18 reference statements)
8
26
0
1
Order By: Relevance
“…The dental profession has not had universal guidelines on how to manage the virus, despite being perceived as having extremely high risk for exposure among all professions 2 , 3 , 4 . However, data from similar studies in Europe and USA showed that the prevalence and the positivity rates among dental professionals/dental hygienists was low, suggesting that current infection control recommendations against COVID-19 could be appropriate [ 8 , 9 , 25 , 26 ]. Similarly, our findings follow the same trend for most countries, where infectivity rate during the performance of the survey could be retrieved ( Tables 2 and 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dental profession has not had universal guidelines on how to manage the virus, despite being perceived as having extremely high risk for exposure among all professions 2 , 3 , 4 . However, data from similar studies in Europe and USA showed that the prevalence and the positivity rates among dental professionals/dental hygienists was low, suggesting that current infection control recommendations against COVID-19 could be appropriate [ 8 , 9 , 25 , 26 ]. Similarly, our findings follow the same trend for most countries, where infectivity rate during the performance of the survey could be retrieved ( Tables 2 and 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…While some countries restricted dental care only to urgencies/emergencies, in others, where the pandemic had subsided or even during the phase of maximum infection rates, dental clinics and offices had returned/continued to also provide non-urgent dental care, but figures from global data are not available. Moreover, limited knowledge at that time, unavailability of tests, availability or incorrect use of personal protective equipment (PPE) and conflicting protocols may have lowered protection among the dental care workforce and patients, potentially increasing the infection rate and transmission 7 , 8 , 9 , 10 . This paper reports findings from the 2020 International Collaborative COVID-19 Disease Study giving, to the best of authors’ knowledge, the only updated worldwide observational epidemiological study on COVID-19 and dental professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies surveyed only dentists; Bontà et al (2020) surveyed only dental hygienists, whereas 3 studies surveyed dentists, dental hygienists, and dental assistants ( Ahmed et al 2020 ; Chaudhary et al 2020 ; Stangvaltaite-Mouhat et al 2020 ). No studies compared responses among the 3 professions to expose differences in their pandemic experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Although all dentists were mindful of the risk of COVID-19, they did not use N95 masks in the dental clinic 25) .…”
Section: Characteristics Of Studies Included In the Reviewmentioning
confidence: 99%